God, Time and the Kalām Cosmological Argument - Bobier, Christopher Alan (Sophia, 2013)
The Kalām cosmological argument deploys the following causal principle: whatever begins to exist has a cause. Yet, under what conditions does something ‘begin to exist’? What does it mean to say that ‘X begins to exist at t’? William Lane Craig has offered and defended various accounts that seek to establish the necessary and sufficient conditions for when something ‘begins to exist.’ I argue that all of the accounts that William Lane Craig has offered fail on the following grounds: either they entail that God has a cause or they render the Kalām argument unsound. Part of the problem is due to Craig’s view of God’s relationship to time: that God exists timelessly without creation and temporarily with creation. The conclusion is that Craig must abandon either the Kalām argument or his view of God’s relationship to time; he cannot consistently hold both.